Comparative assessment of residents' satisfaction with old and new condominiums : case studies from Kuala Lumpur Metropolis, Malaysia - Ogundele, Ashim Oladimeji (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2010)
Urbanization in Peninsular Malaysia has been rapid especially during the last two decades whereby the rate of urbanization has increased from 53.4% in 1991 to 65.4% in 2000. As population growth increases, space becomes limited and the land price also increases. For this reason the need to provide adequate housing for the growing population became a necessity. Therefore, high density housing such as condominium became a response to the growing demand for housing in most Malaysian cities. The rate of construction of condominiums in Malaysia keeps increasing since the last two decades. The number of dilapidated and abandoned condominiums is also increasing while some of them are converted for other uses, which is somewhat a waste of economic resource. The study provides a comparative assessment of residents' satisfaction with condominiums of different ages (the older and the younger condominiums) within the metropolis of Kuala Lumpur, Malaysia, with four (4) basic components grouped as independent variables – dwelling unit features, neighbourhood facilities, residential management and household characteristics. Two hundred (200) respondents participated in the survey exercise with 100 respondents from each Condominium type. Descriptive statistics has been employed to show the socio – economic distribution of the respondents. Findings from the study indicate that the residents of the older condominiums (above 10 years) were not satisfied with the dwelling unit features and the residential management, however, over 40% of the residents are also planning to relocate due to current housing situation. The residents of the younger condominiums (less than 10 years) on the other hand, show a relatively high level of satisfaction with the dwelling unit features and moderately satisfied with the residential management. Spearman's (ρ) correlation has been estimated to determine the extent of the relationship between the residents' satisfaction and the ages of the condominiums. The findings also revealed that ages of the building is a predictor of the assessment. The older condominium showed a more significant relationship between the overall satisfaction and the tested variables compared to the younger condominiums as a result of the age difference. The study further suggests measures which may help enhance management of the condominiums so as to ensure a pleasant living for the condominium residents.